Pengembangan E-Modul Berbasis Photomath untuk Meningkatkan Keterampilan Berpikir Tingkat Tinggi dalam Pembelajaran Matematika - Aminullah Aminullah; Ruwaidah Ruwaidah (Supermat : Jurnal Pendidikan Matematika, 2025)
The development of digital technology has led to innovations in learning methods that not only focus on procedural memorization but also develop Higher Order Thinking Skills (HOTS). One alternative that can be developed is a Photomath-based e-module, an application that guides the systematic and interactive solving of mathematical problems. The purpose of this study is to develop a Photomath-based e-module on quadratic equations and test its validity, practicality, and effectiveness in the learning process. This study uses the ADDIE development model, which consists of the steps of analysis, design, development, implementation, and evaluation. The results of the validation process show that the e-module is highly valid with an average score of 88.3%. Product testing shows progress in learning outcomes, as seen from the change in average scores from 52.3 on the pre-test to 78.6 on the post-test, with an N-Gain of 0.67 (moderate to high category). Student participation in learning activities increased from moderately active to very active, while student responses were very positive, with 85% considering the emodule interesting, easy to use, and helpful in understanding the material. The results of the study show that the emodule is valid, practical, and effective in improving higher-order thinking in mathematics learning.